Treatment effect of Pantawid Pamilya on monitored and non-monitored children of household beneficiaries - Melad, Kris Ann M.
The Pantawid Pamilyang Pilipino Program (Pantawid Pamilya) is the Philippine’s conditional cash transfer program that aims to break the poverty cycle by encouraging poor households to invest in human capital, particularly health and education of children. This is done by providing cash grants to beneficiaries who comply with the program’s education and health conditions. Per household, the program has set a maximum limit of three children who will be monitored for the education condition and will receive corresponding grants if compliant. This policy forces the program to select specific children for monitoring, while other children in the household are non-monitored. This study aims to reveal the effect of the program on education outcomes using an intrahousehold resource allocation model that tries to explain schooling decisions for monitored and non-monitored children in Pantawid households. This is done by estimating the impact of the program on certain education and related outcomes separately for monitored and non-monitored children age 6-11 and 12-15 years old using Regression Discontinuity Design (RDD). Results show that the program generally improves education outcomes of monitored children for both age groups. Non-monitored children of the younger age group are generally unaffected, while non-monitored Pantawid children of the older age group are negatively affected suggesting possible displacement of these children in favor of their siblings who are monitored in the program. There is also evidence that parents’ knowledge on program benefit scheme and monitoring status of their children are important in achievement of desired outcomes in education. In general, the study recommends that the program avoid tagging of specific children as beneficiaries of the program as this may result in unintended consequences on non-monitored children in the Pantawid Pamilya households.